2019
DOI: 10.1097/nan.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition Administration by Critical Care Nurses in Iran

Abstract: In Iran, nurses are responsible for administering parenteral nutrition (PN) to hospitalized patients in intensive care units (ICUs). However, little information is available among nurses in Iran regarding best practices in PN administration. This study evaluates the performance of critical care nurses in Iran in the administration of PN. The performance of 50 nurses in the administration of PN in the ICU was observed 3 times during a 5-month period for a total of 150 observations. A researcher-developed checkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
4
1
1
Order By: Relevance
“…However, slightly less than a third of them did not do this in order to prevent hypoglycemia. This study contradicts the findings of Taherkhani et al (5) , whose research found that Iranian ICU nurses have only rudimentary knowledge of how to handle TPN withdrawal safely. However, Othman & Ahmed (19) found that nurses' practices were bad at Rapareen Public Hospital.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, slightly less than a third of them did not do this in order to prevent hypoglycemia. This study contradicts the findings of Taherkhani et al (5) , whose research found that Iranian ICU nurses have only rudimentary knowledge of how to handle TPN withdrawal safely. However, Othman & Ahmed (19) found that nurses' practices were bad at Rapareen Public Hospital.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that over two thirds of the nurses in the sample were wed. According to Taherkhani et al (5) the majority (or more specifically, two-thirds) of the nurses under study were females, and roughly as many were married.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study by Ameri et al [11], none of the demographic information such as age, work experience, level of education, type of employment, and parenteral nutrition courses influenced the nurses' practices and knowledge scores. A statistical analysis in a study by Taherkhani et al [14] showed no significant difference in the mean score of nurses with different work…”
Section: Resultsmentioning
confidence: 92%
“…Evidenciado este contexto, em 2004, um estudo qualitativo atribuiu as dificuldades provocadas pelo pouco conhecimento dos profissionais sobre a NP e a dificuldade da continuidade do cuidado de enfermagem por esses profissionais 14 . Esse cenário foi ratificado em um estudo do Irã que destacou o pobre conhecimento dos enfermeiros na NP, divergindo dos resultados encontrados neste estudo 18 . Cabe ainda salientar a grande dificuldade de encontrar artigos relacionados às práticas seguras em terapia nutricional em âmbito nacional, o que resulta em um cuidado baseado em diretrizes totalmente internacionais 19 .…”
Section: Discussionunclassified